Neurofilament light chain in serum for the diagnosis of amyotrophic lateral sclerosis - Verde, Federico; Steinacker, Petra; Weishaupt, Jochen H.; Kassubek, Jan; Oeckl, Patrick; Halbgebauer, Steffen; Tumani, Hayrettin; Arnim, Christine A. F. von; Dorst, Johannes; Feneberg, Emily; Mayer, Benjamin; Müller, Hans-Peter; et al. (Journal of neurology, neurosurgery, and psychiatry, 2019)
Objective To determine the diagnostic and prognostic performance of serum neurofilament light chain (NFL) in amyotrophic lateral sclerosis (ALS). Methods This single-centre, prospective, longitudinal study included the following patients: 124 patients with ALS; 50 patients without neurodegenerative diseases; 44 patients with conditions included in the differential diagnosis of ALS (disease controls); 65 patients with other neurodegenerative diseases (20 with frontotemporal dementia, 20 with Alzheimer’s disease, 19 with Parkinson’s disease, 6 with Creutzfeldt-Jakob disease (CJD)). Serum NFL levels were measured using the ultrasensitive single molecule array (Simoa) technology. Results Serum NFL levels were higher in ALS in comparison to all other categories except for CJD. A cut-off level of 62 pg/mL discriminated between ALS and all other conditions with 85.5% sensitivity (95% CI 78% to 91.2%) and 81.8% specificity (95% CI 74.9% to 87.4%). Among patients with ALS, serum NFL correlated positively with disease progression rate (rs=0.336, 95% CI 0.14 to 0.506, p=0.0008), and higher levels were associated with shorter survival (p=0.0054). Serum NFL did not differ among patients in different ALS pathological stages as evaluated by diffusion-tensor imaging, and in single patients NFL levels were stable over time. Conclusions Serum NFL is increased in ALS in comparison to other conditions and can serve as diagnostic and prognostic biomarker. We established a cut-off level for the diagnosis of ALS.
Published online first 11 October 2018
Gesehen am 16.06.2021